Screening and identification of tyrosinase inhibitors in edible plant materials by on-line UPLC-enzyme reactor coupled with UHPLC-FTMS. (1st March 2023) - Fang, Xiao; Dai, Lei; Ding, Tian-Ming; Zhu, Yao; Zan, Jun-Feng; Chen, Lin-Lin; Ding, Xiao-Ping; Liu, Jun-Feng
Highlights: Established a method for identifying tyrosinase inhibitors from the complex matrix. The method avoided false positive activity with good selectivity and sensitivity. The method exhibited excellent tolerance to the sample matrix. The method enabled minimal sample consumption with high analytical efficiency. Several tyrosinase inhibitors were identified from green tea and cinnamon extracts. Abstract: Tyrosinase plays a primary role in melanin biosynthesis and enzymatic browning of freshly cut fruits and vegetables. Herein, an on-line ultraperformance liquid chromatography diode array detector biochemical detection (UPLC-DAD-BCD) method was established to identify trace amount potent tyrosinase inhibitors and antibrowning agents in complex mixtures. The tyrosinase inhibition activities of some representative compounds were evaluated by using the established method and their chromatography-activity relationships were obtained. Then the proposed UPLC-DAD-BCD method was applied to screen tyrosinase inhibitors in edible herbal extracts and identified two tyrosinase inhibitors in green tea and three in cinnamon. The above active ingredients were determined by ultra-high-performance liquid chromatography linear ion trap/orbitrap high resolution mass spectrometry (UHPLC-FTMS). The on-line UPLC-DAD-BCD in combination with UHPLC-FTMS was confirmed to be a powerful technique to screen and elucidate the active ingredients in complex matrixes and could be applied to evaluate the integrated effects of multiple ingredients against corresponding targets.